Application of Number Theory to Determine Congruence in Traffic Lights - Widianna, Andina Ayu; Nabiilah, Salmi Harfi; Jumali, Akhmad Jumali (International Journal of Technology and Modeling, 2022)
One of the important algorithms owned by number theory and related to the nature of this division is the Euclidean algorithm which when applied to congruence can be used as a computation to solve the existing problem. The purpose of this study is to show that the alignment of traffic lights is important because every road user has the same rights, so the calculation for light traffic must be done fairly but not in the same way because the density of roads on each road is different. The research method used by the author is the experimental method.